African Anarchism : a History and Analysis. - Mbah, Sam (See Sharp Press, 1997)
African Anarchism covers a wide range of topics, including anarchistic elements in traditional African socieites, African communalism, Africa's economic and political development, the lintering social, political, and economic effects of colonialism, the development of "African socialism, the failure of "African socialism, and a possible means of resolving Africa's ongoing crises.